INVESTIGATION OF CORROSION-PROTECTIVE PERFORMANCE OF POLYANILINE COVERED INORGANIC PIGMENTS - Khan, M. I.; Hashim, S.; Chaudhry, A. U.; Iqbal, M. Z. (The Nucleus, 2010)
In current work, three types of inorganic pigments i.e. iron oxide (Fe2O3), Zinc oxide (ZnO) and Nickel carbonate (NiCO3) were mixed in equal proportion and surface-modified with inherited electrically conductive polyaniline (phosphate doped polyaniline) by method of in situ polymerization i.e. polymerization of polyaniline in presence of mixed pigments. Ammonium per sulfate was used as an oxidant for polymerization of aniline at low temperature. Fourier Transform Infrared (FTIR) spectroscopy, X-ray Diffraction (XRD) and scanning electron microscopy (SEM) were used to analyze the surface of polyaniline–pigment composites. These characterization techniques revealed that the surface of pigments have been modified by phosphate doped polyaniline. Polyaniline, mixed pigments alone and polyaniline layered mixed pigments were incorporated with solvent based primer of vinyl acrylate and applied on carbon steel panels. Corrosion rate of carbon steel panels obtained after 800 hrs of immersion in 4% sodium chloride. It was least in case of coated samples with coating containing polyaniline modified pigments.